Investigation on Aerodynamic Behaviour of a SUV Car Model with Vortex Generators at Different Yaw Conditions - G. Shankar (Journal of Applied Fluid Mechanics, 2019)
The present work discusses the aerodynamic behaviour of a typical SUV car model mounted with three vortex generators (VGs) similar to the shape of a right-angled triangle in four different yaw angle configurations, the results of which have been quantitatively assessed in the sub-sonic wind tunnel and by using realizable (k- ε) model. The VG positioned in the middle is kept in the fixed state while the yaw position of VGs on either side has been modified and its significance is presented in this article. The pressure distribution data along the central plane of the car model for all the cases have been obtained by using 32 channel digital pressure scanner that is connected with the pressure tapings prepared in the symmetrical plane of the car model. Simultaneously two separate cantilever type load cell setup is used in this work to measure the magnitude of drag and lift force with measuring sensitivity of about 0.01N. From the experiments, it is determined that the car model with outer VGs heading the rear windshield and central plane possess the maximum drag and lift coefficient reduction rate of about 4.35% and 3.23% respectively compared to car model without VGs. In addition to these findings it is also determined that the vehicle model with VGs positioned perpendicular to the wind stream direction exhibited strong drag magnitude than that of the vehicle without VGs. This increased drag can be utilized for rapid deceleration of vehicle motion (Aerodynamic braking) particularly at the instance of vehicle is running at high speed conditions. The realizable (k- ε) model estimated the drag and lift coefficient closer to that of wind tunnel results and exhibited a maximum error deviation of 2.38%. Further, realizable (k- ε) model predicted the existence of the magnitude of velocity gradient, intensity of turbulent kinetic energy variation and streamlined pattern of velocity gradient around the vehicle with VGs compared to the case of vehicle model without VGs at its rear end.